Evolution of telomere maintenance and tumour suppressor mechanisms across mammals. (5th March 2018) - Tian, Xiao; Doerig, Katherine; Park, Rosa; Can Ran Qin, Alice; Hwang, Chaewon; Neary, Alexander; Gilbert, Michael; Seluanov, Andrei; Gorbunova, Vera
Abstract : Mammalian species differ dramatically in telomere biology. Species larger than 5–10 kg repress somatic telomerase activity and have shorter telomeres, leading to replicative senescence. It has been proposed that evolution of replicative senescence in large-bodied species is an anti-tumour mechanism counteracting increased risk of cancer due to increased cell numbers. By contrast, small-bodied species express high telomerase activity and have longer telomeres. To counteract cancer risk due to longer lifespan, long-lived small-bodied species evolved additional telomere-independent tumour suppressor mechanisms. Here, we tested the connection between telomere biology and tumorigenesis by analysing the propensity of fibroblasts from 18 rodent species to form tumours. We found a negative correlation between species lifespan and anchorage-independent growth. Small-bodied species required inactivation of Rb and/or p53 and expression of oncogenic H-Ras to form tumours. Large-bodied species displayed a continuum of phenotypes requiring additional genetic 'hits' for malignant transformation. Based on these data we refine the model of the evolution of tumour suppressor mechanisms and telomeres. We propose that two different strategies evolved in small and large species because small-bodied species cannot tolerate small tumours that form prior to activation of the telomere barrier, and must instead use telomere-independent strategies that act earlier, at the hyperplasia stage. This article is part of the theme issue 'Understanding diversity in telomere dynamics'.